ADMINISTRATIVE SYSTEM OF PAYMENT IN MONEY PAID SCHOOL SENIOR HIGH SCHOOL 100 JAKARTA USING VISUAL BASIC 6.0 - Novy Wahyudiyati; Indrianto Indrianto, SKom, MM (Jurnal Sistem Informasi, 2005)
This writing contains administrative information on the payment of tuition feesSenior High School 100 Jakarta, because there are no tools on the computer thathandles the administration of payments so often experienced difficulties, including:length of student records data and administrative data payment of tuition fees that arenot arranged in order according to with the main number of students.Under these circumstances, the writer makes a system with reference to the currentprocedure. This system is expected to help overcome existing problems in order toimprove efficiency, effectiveness and productivity of work and quality of schools.The author will use the display program Microsoft Visual Basic 6.0.